2006
DOI: 10.1093/ajcn/84.5.1070
|View full text |Cite
|
Sign up to set email alerts
|

Compared with casein or total milk protein, digestion of milk soluble proteins is too rapid to sustain the anabolic postprandial amino acid requirement

Abstract: Our results confirm the major role of kinetics in dietary nitrogen postprandial utilization and highlight the paradox of MSPI, which, despite its high Protein Digestibility Corrected Amino Acid Score, ensures a rate of amino acid delivery that is too rapid to sustain the anabolic requirement during the postprandial period. Milk proteins had the best nutritional quality, which suggested a synergistic effect between soluble proteins and caseins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
129
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 31 publications
14
129
2
1
Order By: Relevance
“…Lacroix et al 11 more recently reported transient hyper-followed by hypo-aminoacidemia and more rapid transfer of dietary nitrogen to serum proteins, serum and urinary urea with whey when compared to micellar casein or total milk protein in adults. These authors concluded that, despite the high Protein Digestibility Corrected Amino Acid Score of the whey proteins, the rate of amino-acid delivery was too rapid to sustain anabolic requirement during the 8-h postprandial period.…”
Section: Discussionmentioning
confidence: 99%
“…Lacroix et al 11 more recently reported transient hyper-followed by hypo-aminoacidemia and more rapid transfer of dietary nitrogen to serum proteins, serum and urinary urea with whey when compared to micellar casein or total milk protein in adults. These authors concluded that, despite the high Protein Digestibility Corrected Amino Acid Score of the whey proteins, the rate of amino-acid delivery was too rapid to sustain anabolic requirement during the 8-h postprandial period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct glucagon-stimulating effect of amino acids (Kabadi, 1991;Claessens et al, 2007), the fall in glucose concentrations due to the higher insulin response induced by the carbohydrate/protein hydrolysate drinks might have contributed to the prolonged glucagon response. Hydrolysates of slowly digestible proteins such as casein may induce faster amino-acid and hormonal responses than the intact protein (Calbet and Holst, 2004;Lacroix et al, 2006). However, for hydrolysates of other proteins that are digested faster, such as whey protein, the difference is smaller Boza et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 On the basis of their absorption pattern, dietary proteins can be divided in so-called fast and slow digestible proteins. 14 Fast proteins, such as whey protein, are soluble, whereas slow proteins, such as casein, clot in the stomach resulting in a delay in gastric emptying 15,16 and lower but more sustained plasma amino-acid elevations after ingestion compared with fast proteins, 14,16,17 which may be associated with differences in hormonal and thermogenic responses. 18 Hall et al 17 found that higher postprandial circulating levels of amino acids are associated with increased satiety and suggested that fast proteins are, therefore, more satiating than slow proteins.…”
Section: Introductionmentioning
confidence: 99%